Chad : Third Review Under the Extended Credit Facility Arrangement, Request for Waiver of Nonobservance of Performance Criterion and Financing Assurances Review-Press Release; Staff Report and Statement by the Executive Director for Chad. (IMF Staff Country Reports; Country Report ;, 2019)
The current ECF arrangement (access of 160 percent of quota or SDR 224.32 million) was approved on June 30, 2017 in the context of a very difficult and deteriorating social, economic, and financial situation. The crisis was precipitated by the oil price and security shocks that began in 2014, and the heavy burden of external commercial debt with Glencore. The restructuring of this debt in June 2018 paved the way for the completion of the second review in July 2018. Chad's stability is key for the regional security situation given its regional peace-keeping efforts.